2002
DOI: 10.2337/diabetes.51.5.1391
|View full text |Cite
|
Sign up to set email alerts
|

Fas/Fas Ligand Interactions Play an Essential Role in the Initiation of Murine Autoimmune Diabetes

Abstract: These results suggest a substantial contribution of Fas/ FasL interactions to CD4؉ , but not CD8 ؉ , T-cell-mediated destruction of pancreatic ␤-cells. When anti-FasL antibody was administered to NOD mice between 5 and 15 weeks of age, the onset of diabetes was slightly delayed but the incidence was not decreased. However, administration of anti-FasL antibody at 2-4 weeks of age completely prevented insulitis and diabetes. These results suggest that Fas/FasL interactions contribute to CD4 ؉ T-cell-mediated ␤-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 38 publications
(31 reference statements)
4
35
0
1
Order By: Relevance
“…26,28,29 Thus, both genetic and pharmacological results directly related the higher presence of CD5 ϩ B cells in the pancreata of NOD mice to inhibition of FasL activity. In addition, consistent with previous results, 27 treatment with FasL-neutralizing mAb halted progression of insulitis in NOD-wt mice compared with control mice ( Figure 3B). …”
Section: Cd5 ϩ B Cells Constitute a Significant Proportion Of B Cellssupporting
confidence: 81%
See 1 more Smart Citation
“…26,28,29 Thus, both genetic and pharmacological results directly related the higher presence of CD5 ϩ B cells in the pancreata of NOD mice to inhibition of FasL activity. In addition, consistent with previous results, 27 treatment with FasL-neutralizing mAb halted progression of insulitis in NOD-wt mice compared with control mice ( Figure 3B). …”
Section: Cd5 ϩ B Cells Constitute a Significant Proportion Of B Cellssupporting
confidence: 81%
“…More important, we found that antibody blockade of FasL protects NOD-wt mice from T1D without causing lymphoproliferation, thereby directly linking the protection to FasL blockade. 26,27 In addition, disease-resistant NOD-gld/ϩ mice harbor diabetogenic T cells that cause disease in NODsevere combined immunodeficiency adoptive hosts. 26 We hypothesize that inactivation of FasL leads to augmentation of an immunoregulatory mechanism that keeps the diabetogenic T cells in check.…”
mentioning
confidence: 99%
“…In addition, the administration of anti-FasL antibody at 2-4 weeks of age to NOD mice prevented insulitis and diabetes. This suggests that Fas/FasL interactions contribute to CD4(þ) T-cell-mediated beta-cell destruction and play an essential role in the initiation of autoimmune diabetes (Nakayama et al, 2002).…”
Section: Pathways Of Caspase Activation In Apoptosismentioning
confidence: 99%
“…Indeed, Fas antibody, FasL antibody, or any other reagents that could decrease the expression and translocation of Fas could be used in blocking apoptosis of an islet. Nakayama et al (2002) demonstrated that administration of anti-FasL antibody at 2-4 weeks of age completely prevented insulitis and diabetes. High glucose-induced apoptosis is due to the interaction between the constitutively expressed FasL and the upregulated Fas.…”
Section: Blocking the Fas And Fasl Pathwaymentioning
confidence: 99%
See 1 more Smart Citation